Step
*
of Lemma
cong-angle-out-exists-iff
∀e:BasicGeometry. ∀a,b,c,x,y,z:Point.
  ((((b ≠ a ∧ b ≠ c) ∧ y ≠ x) ∧ y ≠ z)
  
⇒ (abc ≅a xyz 
⇐⇒ ∃a',c',x',z':Point. ((((out(b a'a) ∧ out(b c'c)) ∧ out(y x'x)) ∧ out(y z'z)) ∧ a'bc' ≅a x'yz')))
BY
{ Auto }
1
1. e : BasicGeometry
2. a : Point
3. b : Point
4. c : Point
5. x : Point
6. y : Point
7. z : Point
8. b ≠ a
9. b ≠ c
10. y ≠ x
11. y ≠ z
12. abc ≅a xyz
⊢ ∃a',c',x',z':Point. ((((out(b a'a) ∧ out(b c'c)) ∧ out(y x'x)) ∧ out(y z'z)) ∧ a'bc' ≅a x'yz')
2
1. e : BasicGeometry
2. a : Point
3. b : Point
4. c : Point
5. x : Point
6. y : Point
7. z : Point
8. b ≠ a
9. b ≠ c
10. y ≠ x
11. y ≠ z
12. ∃a',c',x',z':Point. ((((out(b a'a) ∧ out(b c'c)) ∧ out(y x'x)) ∧ out(y z'z)) ∧ a'bc' ≅a x'yz')
⊢ abc ≅a xyz
Latex:
Latex:
\mforall{}e:BasicGeometry.  \mforall{}a,b,c,x,y,z:Point.
    ((((b  \mneq{}  a  \mwedge{}  b  \mneq{}  c)  \mwedge{}  y  \mneq{}  x)  \mwedge{}  y  \mneq{}  z)
    {}\mRightarrow{}  (abc  \mcong{}\msuba{}  xyz
          \mLeftarrow{}{}\mRightarrow{}  \mexists{}a',c',x',z':Point
                    ((((out(b  a'a)  \mwedge{}  out(b  c'c))  \mwedge{}  out(y  x'x))  \mwedge{}  out(y  z'z))  \mwedge{}  a'bc'  \mcong{}\msuba{}  x'yz')))
By
Latex:
Auto
Home
Index